2017
DOI: 10.1101/123497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic post-transcriptional regulation during embryonic stem cell differentiation

Abstract: During in vitro differentiation, pluripotent stem cells undergo extensive remodeling of their gene expression. While studied extensively at the transcriptome level, much less is known about protein dynamics, which can differ significantly from their mRNA counterparts. Here, we present genome-wide dynamic measurements of mRNA and protein levels during differentiation of embryonic stem cells (ESCs). We reveal pervasive discordance, which can be largely understood as a dynamic imbalance due to delayed protein syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Although differences in NANOG, OCT4A, and SOX2 mRNA expressions were detectable between the groups at different time points, only NANOG was detectable on protein level, in line with earlier reports on dissimilar NANOG, OCT4A, and SOX2 protein and mRNA expression dynamics within mesenchymal stem/progenitor cells [54][55][56]. This AA/retinol-induced increase in the NANOG, especially in the presence of controlled inflammatory stimuli at 3 days, could be ascribed primarily to the capability of AA and retinol to activate the ten-eleven translocation (TET) DNA demethylases, initiating intracellular epigenetic reprogramming with pluripotency amplification [20,57].…”
Section: Discussionsupporting
confidence: 91%
“…Although differences in NANOG, OCT4A, and SOX2 mRNA expressions were detectable between the groups at different time points, only NANOG was detectable on protein level, in line with earlier reports on dissimilar NANOG, OCT4A, and SOX2 protein and mRNA expression dynamics within mesenchymal stem/progenitor cells [54][55][56]. This AA/retinol-induced increase in the NANOG, especially in the presence of controlled inflammatory stimuli at 3 days, could be ascribed primarily to the capability of AA and retinol to activate the ten-eleven translocation (TET) DNA demethylases, initiating intracellular epigenetic reprogramming with pluripotency amplification [20,57].…”
Section: Discussionsupporting
confidence: 91%
“…While initial work focused on epigenetic mechanisms, we now appreciate that transcriptional events do not entirely determine cellular identity. Recent studies have revealed that diverse post-transcriptional mechanisms influence the functional output of genetic programs (i.e., proteome content) required by stem cells (Nilsen and Graveley, 2010;van den Berg et al, 2017;Williamson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This could be because of the alignment of the datasets or because of the different labeling procedures of the datasets. That is, the PBMC-FACS data was labeled based on the expression of cell surface markers instead of clustering the cells, and it is known that protein and gene expression poorly correlated [27,28], which might explain these results.…”
Section: Discussionmentioning
confidence: 99%